2013
DOI: 10.5194/acp-13-5715-2013
|View full text |Cite
|
Sign up to set email alerts
|

Production of methyl vinyl ketone and methacrolein via the hydroperoxyl pathway of isoprene oxidation

Abstract: The photo-oxidation chemistry of isoprene (ISOP; C5H8) was studied in a continuous-flow chamber under conditions such that the reactions of the isoprene-derived peroxyl radicals (RO2) were dominated by the hydroperoxyl (HO2) pathway. A proton-transfer-reaction time-of-flight mass spectrometer (PTR-TOF-MS) with switchable H3O+ and NO+ reagent ions was used for product analysis. The products methyl vinyl ketone (MVK; C4H Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
203
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(221 citation statements)
references
References 59 publications
16
203
2
Order By: Relevance
“…Liu et al (2013) implemented this technique successfully in their laboratory study using SRI-ToFMS, resulting in a lower yield than previously reported for MAC and MVK in the low-NO oxidation of isoprene. Field application may prove more challenging, however, as the trapping is labor intensive and requires careful humidity control to avoid ice buildup and blockage.…”
Section: Analytical Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al (2013) implemented this technique successfully in their laboratory study using SRI-ToFMS, resulting in a lower yield than previously reported for MAC and MVK in the low-NO oxidation of isoprene. Field application may prove more challenging, however, as the trapping is labor intensive and requires careful humidity control to avoid ice buildup and blockage.…”
Section: Analytical Challengesmentioning
confidence: 99%
“…These uncertainties stem from, for example, the large range in reported yields for isoprene nitrates (4-15 %) (Paulot et al, 2009a), disagreements up to 90 % in reported MAC and MVK yields from the low-NO pathway (Liu et al, 2013, and references therein), various proposed sources of SOA from the high-NO pathway Kjaergaard et al, 2012;Lin et al, 2013), missing contributions to SOA mass from the low-NO pathway , uncharacterized fates of oxidized species like HPALDs (which may have isomer dependence), incomplete understanding of oxygen incorporation (Peeters et al, 2009;Crounse et al, 2013), and under-characterized impact of RO 2 lifetimes on chamber results . The OH oxidation of α-pinene (Eddingsaas et al, 2012) and other monoterpenes is less well characterized than that of isoprene, but, in general, proceeds through analogous steps.…”
Section: Oh Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…During the dry season the ratio of methyl vinyl ketone + methacrolein + hydroperoxides (MVK + MAC + ISOPOOH) (Liu et al, 2013) to isoprene was higher compared to the dry-to-wet transition and the wet season (data not shown). This higher ratio may indicate an increased oxidative capacity of the atmosphere during the dry season.…”
Section: Seasonal Variation On Isoprenoid Mixing Ratios and Emissionsmentioning
confidence: 99%
“…The new scheme also includes an update for the aerosol reactive uptake coefficient of NO 3 radicals, in which the value is increased from 10 −4 to 0.1 (Mao et al, 2013b). Beyond Mao et al (2013b), we also change the stoichiometry of the (ISOPO 2 + HO 2 ) reaction to that recommended by the laboratory study of Liu et al (2013), which has smaller uncertainties and leads to relatively smaller yields (by ∼ 50 %) of HO x , methyl vinyl ketone, and methacrolein from this pathway. Our work tests the sensitivity of model results to these updates in the isoprene photo-oxidation mechanism.…”
Section: Isoprene Photo-oxidation Mechanismmentioning
confidence: 99%